A MODEL-THEORETICAL ANALYSIS FOR DIGITAL TAX ADMINISTRATIONS (International Journal of Innovative Technologies in Economy, 2021)
Fairness in the sense of tax equality is a fundamental principle in modern tax systems. In recent years tax administrations have been making tremendous advances in moving from paper tax returns to a far-reaching digitalisation of the taxation procedure. This paper represents the first attempt to examine the impact of digitalisation of the tax administration on fair taxation through model theory. The model suggested in this paper is based on Allingham and Sandmo’s tax evasion model (Allingham & Sandmo, 1972, 323–338) supplemented by psychological costs of tax evasion and compliance costs and then transferred to the context of digitalisation and fair taxation. The model is intended to mathematically derive the influence of various digitalisation measures on the taxpayer's decision to behave fairly. It implies that the objective of fair taxation should be promoted with a mix of deterrent and encouraging measures.